Economic Impacts of Agricultural Technology Use on Rice Production Value in Mechanized Paddy Systems - Ansar; Yusriadi; Suherman (Edupedia Publisher, 2025)
Agricultural technology adoption is widely promoted to improve rice productivity; however, its economic impacts within mechanized farming systems remain insufficiently understood from a system-level perspective. This study addresses this gap by examining how technology use influences rice production value within integrated paddy systems. A cross-sectional survey of rice farmers operating in mechanized lowland systems was conducted. Data were analyzed using a multiple linear regression framework to assess the economic effects of agricultural technology use alongside conventional production inputs, with production value employed as the primary performance indicator. The results indicate that agricultural technology use positively influences rice production value, although impacts vary across technology types. Technologies addressing critical production constraints exhibit stronger economic effects than labor-substituting tools. The overall model demonstrates high explanatory power, confirming the relevance of technology adoption within the broader farming system. The findings suggest that technology contributes to economic performance through efficiency-enhancing pathways and improved resource allocation rather than uniform input intensification, highlighting the importance of system coherence. This study provides empirical evidence that context-specific and integrated technology adoption strengthens economic efficiency and supports sustainable mechanized rice farming systems.